Discrimination in Latin America: An elephant in the room? - Alberto Chong; Hugo \~Nopo (Inter-American Development Bank, Research Department, 2007)
This paper surveys evidence on discrimination in Latin America and shows that there is a widespread perception of discrimination, especially against the poor, the uneducated and those who lack connections. The channels through which discrimination occurs may be built on the basis of economic factors. However, while perception surveys may be informative, they are less than ideal at helping pinpoint the extent and mechanisms related. Recent experimental evidence suggests little room for discriminatory practices in the region. This puzzle, where individuals perceive discrimination is in the air, but few act discriminatorily, is consistent with an explanation about stereotyping that vanishes when information flows operate well.
Keywords: J15; J16; J71; C93; O54; 330; Economic Experiments; Discrimination; Latin America; Diskriminierung; Lateinamerika